In vitro and in vivo characterization of the antimalarial lead compound SSJ-183 in Plasmodium models - Schleiferböck S; Scheurer C; Ihara M; Itoh I; Bathurst I; Burrows JN; Fantauzzi P; Lotharius J; Charman SA; Morizzi J; Shackleford DM; White KL; et al. (Dove Medical Press, 2013)
Sarah Schleiferböck,1,2 Christian Scheurer,1,2 Masataka Ihara,3,4 Isamu Itoh,3,4 Ian Bathurst,5,† Jeremy N Burrows,5 Pascal Fantauzzi,5 Julie Lotharius,5 Susan A Charman,6 Julia Morizzi,6 David M Shackleford,6 Karen L White,6 Reto Brun,1,2 Sergio Wittlin1,21Swiss Tropical and Public Health Institute, Basel, 2University of Basel, Basel, Switzerland; 3Drug Discovery Science Research Center, Hoshi University, Shinagawa, Tokyo, Japan; 4Synstar Japan Co, Ltd, Odawara, Japan; 5Medicines for Malaria Venture, Geneva, Switzerland; 6Centre for Drug Candidate Optimisation, Monash Institute of Pharmaceutical Sciences, Parkville, VIC, Australia †Ian Bathurst passed away on 26 June 2011Abstract: The objective of this work was to characterize the in vitro (Plasmodium falciparum) and in vivo (Plasmodium berghei) activity profile of the recently discovered lead compound SSJ-183. The molecule showed in vitro a fast and strong inhibitory effect on growth of all P. falciparum blood stages, with a tendency to a more pronounced stage-specific action on ring forms at low concentrations. Furthermore, the compound appeared to be equally efficacious on drug-resistant and drug-sensitive parasite strains. In vivo, SSJ-183 showed a rapid onset of action, comparable to that seen for the antimalarial drug artesunate. SSJ-183 exhibited a half-life of about 10 hours and no significant differences in absorption or exposure between noninfected and infected mice. SSJ-183 appears to be a promising new lead compound with an attractive antimalarial profile.Keywords: antimalarial studies, cross-resistance, stage-specificity, Plasmodium falciparum